Associations Between Variations in Accumulated Workload and Physiological Variables in Young Male Soccer Players Over the Course of a Season - Nobari, Hadi; Alves, Ana Ruivo; Clemente, Filipe Manuel; Pérez-Gómez, Jorge; Clark, Cain C. T.; Granacher, Urs; Zouhal, Hassane (Frontiers in Physiology, 2021)
This study sought to analyze the relationship between in-season training workload with changes in aerobic power (VO2max), maximum and resting heart rate (HRmax and HRrest), linear sprint medium (LSM), and short test (LSS), in under-16 soccer players. We additionally aimed to explain changes in fitness levels during the in-season through regression models, considering accumulated load, baseline levels, and peak height velocity (PHV) as predictors. Twenty-three male sub-elite soccer players aged 15.5±0.2 years (PHV: 13.6±0.4 years; body height: 172.7±4.2 cm; body mass: 61.3±5.6 kg; body fat: 13.7±3.9%; VO2max: 48.4±2.6 ml.kg-1.min-1), were tested three times across the season (i.e., early-season (EaS), mid-season (MiS), and end-season (EnS) for VO2max, HRmax, LSM, and LSS. Aerobic and speed variables gradually improved over the season and had a strong association with PHV. Moreover, the HRmax demonstrated improvements from EaS to EnS; however, this was more evident in the intermediate period (from EaS to MiS) and had a strong association with VO2max. Regression analysis showed significant predictions for VO2max (F (2, 20) = 8.18, P ≤ 0.001) with an R2 of 0.45. In conclusion, the meaningful variation of youth players’ fitness levels can be observed across the season, and such changes can be partially explained by the load imposed.